Honorons Honoré : Honoré Daumier (1808 1879 ) - Bertels, Philippe; De Lepeleire, Damien; Rosa, Bruno Di; Theys, Hans; Turin, Aldo Guillaume; Zacharopoulos, Denys (Mechelen : Cultuurcentrum Mechelen, 2008)
Daumier, Honoré ; Van den Abeele, Michael ; Aëgerter, Laurence ; Aguirre, Philip ; Andrews, Nick ; Antoine, Elodie ; Baete, Julien ; Beaucarne, Boris ; Beaudry, Charlotte ; Belmont, Cécile ; Benault, Stéphane ; Bernier, Pascal ; Bernadet, Jean-Baptiste ; Bertels, Philippe ; Bertrand, Corinne ; Bijl, Guillaume ; Boiy, Tomas ; De Brouwer, Amélie ; Bru, Lucia ; Casaer, Paul ; De Clercq, Bart ; Coez, Cathy ; Colson, Vaast ; Courcelles, Pascal ; Croes, Eric ; Curlet, François ; Daems, Anne ; Dans, Michael ; d'Ansembourg, Sophie ; Denis, Filip ; Devos, Danny ; Devriendt, Robert ; van Dijck, Bart ; d'O, Honoré ; Doriath, Arnaud ; Van Dorpe, Stijn ; Enoki, Yoko ; Estève, Lionel ; Felga, Celine ; François, Michel ; Geens, Lode ; Geronnez, Alain ; Geyskens, Vincent ; Gillain, Céline ; Gillen, Tina ; De Gobert, Philippe ; Guns, Patrick ; Heck, Kati ; Hendrikse, Paul ; Jacovoni, Benedetta ; Janssens, Djos ; Janssens, Philip ; Janssens, Ann Veronica ; Kandilaptis, Babis ; Klagsbrun, Viviane ; Koester, Matthias ; Kowatch, Jeff ; Laute, Vincent ; Lampert, Kirsten ; Lanners, Boudi ; De Lepeleire, Damien ; Liekens, Tom ; Lizein, Annick ; Lohaus, Bernd ; Loos, Ruth ; Lopes, Laone Dos Santos ; Lopez Menchero, Emilio ; Mahéo, Erwan ; Van Mechelen, Jan ; Moerman, Jean-Luc ; Motte, Grégoire ; Mouffe, Michel ; Mounier, Marie Le ; Mroczek, Kenneth Andrew ; Naveau, Nadia ; Noiret-Thomé, Xavier ; Nuku, George ; Nys, Sophie ; Park, Douglas ; Van Parys, Yoann ; Pochetti, Andrea ; Police, Benoit ; Quint, Robert ; Reuzé, Sébastien ; Robbe, Bruno ; Robin, Gwendoline ; Rombouts, Guy ; Rossignol, Marc ; Ryslavy, Kurt ; Saintagnan, Eléonore ; Van San, Tamara ; Segers, Lieven ; Segers, Tim ; Serneels, Stefan ; Singh, Kiran ; Spriet, Jérôme ; Stevenart, Olivier ; etc.
Honorons Honoré, De Garage, ruimte voor actuele kunst, Cultuurcentrum Mechelen, Mechelen, 2008-09-27. 2008-11-23
boek